Contribution to research on the student population at the turn of the nineteenth and twentieth centuries: the first Muslim students from Bosnia and Herzegovina at the University of Zagreb (1874–1914) - Kale, Slaven (Balcanica Posnaniensia. Acta et studia, 2025)
As there was no university in Bosnia and Herzegovina in the period before the First World War, young people, including Muslims, who wished to pursue higher education, had to leave the country. Most frequently, they chose universities in Vienna, Graz and Zagreb. The latter was the nearest university within the Austro-Hungarian Monarchy and enabled them to study without a language barrier. For the Austro-Hungarian authorities, who were then expanding the administration in the newly acquired territory, educated officials were needed; hence, a considerable number of former Muslim students at the University of Zagreb went on to hold important positions in the judiciary and administration of Bosnia and Herzegovina after graduation. In this study, based on the matriculation registers of the University of Zagreb from 1874–1914, the population of Muslim students is presented for the first time. Most of the Muslim students at this university chose to study at the Faculty of Law, while only a few enrolled at the Faculty of Philosophy. Whereas in the last decade of the nineteenth century only a handful of Muslim students studied in Zagreb, their numbers gradually increased, reaching several dozen annually on the eve of the First World War. It is worth noting that the vast majority of Muslim students in Zagreb studied for only a few semesters – on average four – and continued their education at other universities in the Monarchy, most often in Vienna. Almost half of the Muslim students were able to cover their study expenses thanks to scholarships they received, as well as exemptions from tuition fees. The overwhelming majority declared Croatian as their mother tongue, a small number declared Serbian, while none identified Bosnian. At the end of the article, a brief overview is given of the places of employment of the most prominent Muslim students of Zagreb.